THE EFFECT OF ROA, NPM, EVA, AND MVA ON STOCK RETURN ON MANUFACTURING COMPANIES IN THE AUTOMOTIVE SUBSECTOR 2010-2019 - Kurnianti, Destria; Suherman; Wardani, Arnianggi Kurnia (Jurnal Ilmiah Econosains, 2023)
This study aims to determine the effect of ROA, NPM, EVA, and MVA on stock returns in automotive manufacturing companies for the 2010-2019 period. The sample of this research is 7 manufacturing companies in the automotive sub-sector for the 2010-2019 period in Indonesia (38 observations). This research uses unbalanced panel data with a Fixed Effect Model approach. The theory used in this research is signal theory. Testing the data using panel data regression test, classical assumption test, coefficient of determination test, and hypothesis t-test. The test results show that Return On Assets (ROA) has a significant positive effect partially on stock returns, while Net Profit Margin (NPM), Economic Value Added (EVA), and Market Value Added (MVA) partially have a negative effect on stock returns.